2014
DOI: 10.1176/appi.ps.201200470
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness RCT of a CBT Intervention for Youths Who Lost Parents in the Sichuan, China, Earthquake

Abstract: Short-term CBT group intervention seems to be a robust intervention for natural disaster victims. Short-term CBT group intervention was more effective than the general supportive intervention and the no-treatment group in enhancing psychological resilience and reducing PTSD and depression among adolescents who had lost parents in the earthquake. The general supportive intervention was effective only in improving psychological resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 11 publications
2
80
1
Order By: Relevance
“…Short-term cognitive-behavioral therapy (CBT) group intervention represents a robust intervention for natural disaster victims (Y. Chen, Shen, et al, 2014). A randomized waiting-list controlled pilot study was conducted at the site of the Sichuan earthquake in Beichuan County between December 2009 and March 2010 to evaluate the efficacy of narrative exposure therapy (NET) as a short-term treatment for PTSD.…”
Section: Treatment Of Ptsd In Wenchuan Earthquake Survivors Psychothementioning
confidence: 99%
“…Short-term cognitive-behavioral therapy (CBT) group intervention represents a robust intervention for natural disaster victims (Y. Chen, Shen, et al, 2014). A randomized waiting-list controlled pilot study was conducted at the site of the Sichuan earthquake in Beichuan County between December 2009 and March 2010 to evaluate the efficacy of narrative exposure therapy (NET) as a short-term treatment for PTSD.…”
Section: Treatment Of Ptsd In Wenchuan Earthquake Survivors Psychothementioning
confidence: 99%
“…There is a dearth of programs targeting PWID that included mental health support or involved clinical psychologists and social workers. Cognitive behavioral therapy (CBT) has been applied effectively in reducing depression among patients with major depressive disorders (Zu et al, 2014) and among youths who lost parents in the Sichuan earthquake (Chen et al, 2014); no studies have reported application of CBT among PWID in China. Furthermore, evidence-based positive psychological intervention (Seligman and Csikszentmihalyi, 2000;Seligman et al, 2005) is another promising approach.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, one session of CBT per week was conducted for 12 weeks and each session lasted 45 min. The adapted CBT has been widely used in the treatment of PTSD in the Chinese population . In sessions 1–2, the treatment procedure was introduced, cognitive training was conducted, etiology and symptomatology of PTSD were identified, but avoidance should be omitted because our previous experience has shown that PTSD symptoms might be exacerbated if avoidance was addressed.…”
Section: Methodsmentioning
confidence: 99%